Residual stress testing of weld specimens - Tan, Kailun (2017)
Residual stress caused by welding is invisible to the naked eye and requires sophisticated tools and techniques to detect. Very often, these techniques are destructive in nature and the procedure may be costly or impossible to perform especially for very large scale test subjects or those with complex geometries. This project explored the ability of using Non-Destructive Techniques (NDT) to test for residual stress in a mild carbon steel specimen fabricated by butt-welding two identical pieces of mild carbon steel plates together at its centre. Various NDT tests were conducted both on and along the weld line, as well as corresponding areas away from the weld line and the results were compared. A total of three NDT were performed on the specimen namely ultrasound, eddy current and X-ray diffraction. The purpose is to determine if ultrasound and eddy current testing are able to reasonably detect and measure the amount of residual stress present in the specimen.